The Hybrid Work Model and Its Impact on Employee Engagement : A Literature Review Study on the Millennial Generation - Rohmawan Rohmawan; Suharto Suharto; Mochamad Syafii (Lembaga Pengembangan Kinerja Dosen, 2025)
This study investigates the impact of the hybrid work model on employee engagement, with a specific focus on the millennial generation. As organizations continue to adopt flexible work arrangements in the post pandemic era, understanding how these models influence engagement is essential. The primary problem addressed in this research is the lack of clarity on how hybrid work structures affect the psychological, emotional, and behavioral aspects of millennial engagement. The objective is to synthesize existing literature and identify the mechanisms that foster engagement within hybrid environments. A systematic literature review methodology was applied, analyzing 20 peer reviewed journal articles published between 2020 and 2025. The review identifies five key hybrid work components: autonomy and flexibility, digital leadership, work life integration, effective communication, and continuous learning. These elements are found to significantly enhance millennial engagement when implemented intentionally. The synthesis reveals that hybrid work supports millennial needs for autonomy, purpose, relational trust, and growth, which are crucial to sustaining engagement and organizational identification. This study concludes that the hybrid work model, when strategically aligned with generational expectations, serves as a viable approach to maintaining high levels of employee engagement. Future studies are encouraged to explore cross cultural and longitudinal perspectives to deepen understanding and optimize hybrid engagement frameworks.